IMPLEMENTING THE PAPER CORE CREATIVE CYCLE IN THREE-DIMENSIONAL ART LEARNING FOR JUNIOR HIGH SCHOOL STUDENTS - Pramudya, Septya; Gunadi (Eduarts: Jurnal Pendidikan Seni, 2026)
This study explores the creative recycling of paper core waste as an alternative medium in three-dimensional art learning for ninth-grade students at SMP Negeri 1 Pabelan, Semarang Regency. The use of environmentally friendly and easily accessible materials like paper core serves not only as a medium for artistic creation but also as a tool to instill educational values. The study aims to describe the implementation process of using paper core in three-dimensional art projects, analyze the resulting student artworks, and identify the educational values fostered through this learning activity. Employing a qualitative descriptive approach, data were collected through observations, interviews, and documentation. The findings reveal that the learning process was conducted in collaborative groups, where students designed, constructed, and decorated three-dimensional artworks such as pencil holders, piggy banks, and vases from paper core. The resulting artworks demonstrated originality, creativity, and aesthetic quality, reflecting the students’ imaginative engagement with the material. Furthermore, the learning process successfully embedded values such as environmental awareness, collaboration, independence, and creative thinking. This study shows that the creative use of paper core waste in art education not only enhances students’ artistic skills but also promotes sustainable practices and character development. The integration of local materials and recycled media in formal education offers a meaningful and innovative approach to teaching visual arts in schools.